Factors influencing participation in cardiac rehabilitation programmes after referral and initial attendance: qualitative systematic review and meta-synthesis. (October 2013) - Clark, Alexander M; King-Shier, Kathryn M; Spaling, Melisa A; Duncan, Amanda S; Stone, James A; Jaglal, Susan B; Thompson, David R; Angus, Jan E
Background: Greater participation in cardiac rehabilitation improves morbidity and mortality in people with coronary heart disease, but little is understood of patients' decisions to participate. Methods: To develop interventions aimed at increasing completion of programmes, we conducted a qualitative systematic review and meta-synthesis to explore the complex factors and processes influencing participation in cardiac rehabilitation programmes after referral and initial access. To be included in the review, studies had to contain a qualitative research component, population specific data on programme participation in adults> 18 years, and be published ≥1995 as full articles or theses. Ten databases were searched (31 October 2011) using 100+ search terms. Results: Of 2264 citations identified, 62 studies were included involving: 1646 patients (57% female; mean age 64.2), 143 caregivers, and 79 professionals. Patients' participation was most strongly influenced by perceptions of the nature, suitability and scheduling of programmes, social comparisons made possible by programmes, and the degree to which programmes, providers, and programme users met expectations. Women's experiences of these factors rendered them less likely to complete. Comparatively, perceptions of programme benefits had little influence on participation. Conclusions: Factors reducing participation in programmes are varied but amenable to intervention. Participation should be viewed as a 'consumer behaviour' and interventions should mobilize family support, promote 'patient friendly' scheduling, and actively harness the social, identity-related, and experiential aspects of participation.